2019
DOI: 10.1016/j.jagp.2019.01.215
|View full text |Cite
|
Sign up to set email alerts
|

Mild Behavioral Impairment as a Marker of Cognitive Decline in Cognitively Normal Older Adults

Abstract: The CogTrack TM System is proprietary to Wesnes Cognition Ltd (www.wesnes.com). Keith Wesnes owns Wesnes Cognition Ltd and consults for various companies involved in clinical trials. Helen Brooker is employed by Wesnes Cognition Ltd. Clive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
165
4
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 166 publications
(184 citation statements)
references
References 38 publications
12
165
4
3
Order By: Relevance
“…The prevalence of MBI (18.2%) in our cognitively normal participants was higher than that reported by Creese (39) in the PROTECT study, in which 10% of community dwelling older adults aged 50 or over (n = 9,931) reported MBI, as captured by the MBI-C. In a clinical sample of Spanish primary care patients who validated the current cut-points, the prevalence was 5.8% in cognitive normal older adults with subjective complaints (20) and 14.2% in MCI (40).…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence of MBI (18.2%) in our cognitively normal participants was higher than that reported by Creese (39) in the PROTECT study, in which 10% of community dwelling older adults aged 50 or over (n = 9,931) reported MBI, as captured by the MBI-C. In a clinical sample of Spanish primary care patients who validated the current cut-points, the prevalence was 5.8% in cognitive normal older adults with subjective complaints (20) and 14.2% in MCI (40).…”
Section: Discussioncontrasting
confidence: 83%
“…A recently published 5-year longitudinal study demonstrated a higher rate of incident dementia in MBI compared to late life psychiatric illness, demonstrating the clinical significance of the MBI syndrome, and the importance in distinguishing it from psychiatric illness recurring in late life [15]. Additionally, in a large community sample of cognitively unimpaired participants, MBI demonstrated an associated with faster decline in attention and working memory [16]. Recent genetic evidence has also demonstrated a common etiology between MBI and AD, suggesting that neurodegeneration may contribute to the emergence of neuropsychiatric symptoms, as it does with emergent neurocognitive symptoms [17].…”
Section: Introductionmentioning
confidence: 94%
“…Using the MBI-C in a primary care population, MBI prevalence was determined to be 5.8% in SCD (Mallo et al, 2018b), and 14.2% in MCI (Mallo et al, 2018a), with cut points of 8.5 and 6.5 respectively demonstrating acceptable sensitivity and specificity for clinically diagnosed MBI according to the ISTAART diagnostic criteria (Mallo et al, 2018b). Subsequent work has shown that the 8.5 cut point is also associated with subtle cognitive decline in healthy older adults (Creese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%